THE BEGINNING CLASS HAS A DEFECT IN VISION THE STRUCTURE OF THE DEVELOPMENT OF CREATIVE POTENTIAL IN VOLUNTEERS - Akobirova Malika Bo‘ronovna (Western European Studies, 2024)
This article expresses a number of scientific studies on the development of effective models of the development of creative abilities of students of Primary School junior school age, improving the methodology for the development of creative potential in educators through the harmonious content of critical and creative thinking. The development of diagnostic tools for the formation of creative potential in students with visual impairment of the primary class, the improvement of the pedagogical foundations of the design of the creative educational environment are gaining special relevance. The article covers the expression of creative techniques in the field of talim in students with visual impairments
Keywords: krti; tahlil-sintetik; qiyos-taqqos; diagnostika